Gambaran Diri Penderita Kusta di Puskesmas Kunduran Kabupaten Blora Jawa Tengah - Simamora, Kornelia B; Pangastuti, Heny Suseani; Effendy, Christantie (Jurnal Ilmu Keperawatan, 2007)
Please refer to the file